Pelatihan Sistem Informasi Kependudukan Untuk Peningkatan Efisiensi Pencatatan Data Penduduk Desa Darmasari Melalui Program Kuliah Kerja Nyata (KKN) Bina Desa - Toriq Alfan Yasir; Tegar Alfarisy; Yeni Widya Kartika; Mareta Julia Saputri; Fathul Nurul Azmi; Intan Rodiah Safitri; Devi Yanto; Lusi Handayani; Arifanisa; Amrina Rossada; Yayan adiacma; Darmawan, Muhammad Iman (Universitas Hamzanwadi, 2024)
The development of information technology today has had a significant impact in various sectors of life, including in the management of village government administration. Technology facilitates the process of delivering information that is fast, accurate, and not limited by time and place. Darmasari Village, which is part of Pemangkat Subdistrict, experiences several challenges in population administration services, such as inefficiency in recording and managing population data. Through the Bina Desa Community Service Program (KKN), training on population information systems is expected to improve efficiency in recording population data. The implementation of the population information system aims to simplify administrative processes and accelerate public services, and ensure data transparency that can be accessed by the community without the need to come directly to the village office. With this training, it is hoped that village officials can be more effective in carrying out their duties, and improve the quality of services to the people of Darmasari Village.